Evaluating the Effectiveness of CAPM and APT for Risk Measuring and Assets Pricing - Afzal, Fahim; Haiying, Pan (Financial Risk and Management Reviews, 2020)
Persistent with the problem of quantifying the risk associated with securities, this study examines the applicability and validity of Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Theory (APT) while evaluating the stock prices and returns of listed companies in the Pakistan stock exchange. While examining the applicability of CAPM and APT, this study considers the stock return of top ten sectors listed in stock exchange from the period of 2014 to 2019. The result shows that the application of APT for risk estimations may not be showing satisfactory results from the observed data. On average, the p-value is more than 30% for all factors which should be less than 5%. Therefore, in order to compare the application of methods and find out the stock risk, it can be concluded that CAPM approach is more reliable than APT. Thus, it is suggested to adopt the CAPM approach to estimate the realistic stock returns. Additionally, the investor can also consider different indigenous and exogenous economic factors according for calculating market risk and maximizing the return.